Neonatal Hypoglycemia Related to Glycine Levels in Uncontrolled Gestational Diabetes Mellitus during Mid-Late Pregnancy: Multicenter, Prospective Case-Cohort Observational Study - Jiang, Fangfang; Wang, Jianying; Chen, Yao; Cao, Jianyong; Xie, Dan; Su, Zhaojuan; Chen, WuJuan; Liu, Meijun; Bao, Xin; Zhang, Hanxi; Liu, Wei; Yang, Yaochao; et al. (Journal of diabetes research, 2020)
Aims. To explore the relationship between gestational diabetes mellitus (GDM) and neonatal cord blood amino acid and carnitine levels after GDM was diagnosed among pregnant women monitoring glycosylated haemoglobin levels of 5.5%-6.4% during mid-late gestation. Methods. In all, 7289 qualified participants were recruited and divided into two groups (GDM and control groups) between 1 July 2015 and 1 July 2020, and all maternal-neonatal data were collected and analyzed at three centers. Results. Interestingly, glycine in cord blood was not only significantly different between groups (15.52 vs. 6.67, P<0.001) but also associated with neonatal hypoglycemia (r=0.132, P<0.001). Although glycine was an independent positive factor with neonatal hypoglycemia, it had lacked effective size to predict the risk of neonatal hypoglycemia (b=0.002, P<0.001). Conclusion. The study identifies some differences and relationships in maternal-neonatal data when the GDM group has fluctuating glycosylated haemoglobin levels of 5.5%-6.4% without hypoglycemic drug intervention, compared with the control group. Although umbilical cord blood of glycine levels has a lack of effective power to predict the risk of neonatal hypoglycemia, it is probably an independent factor involved in the maternal-neonatal glucolipid metabolism.